2023
DOI: 10.1038/s41467-023-38783-0
|View full text |Cite
|
Sign up to set email alerts
|

A neonatal mouse model characterizes transmissibility of SARS-CoV-2 variants and reveals a role for ORF8

Abstract: Small animal models have been a challenge for the study of SARS-CoV-2 transmission, with most investigators using golden hamsters or ferrets. Mice have the advantages of low cost, wide availability, less regulatory and husbandry challenges, and the existence of a versatile reagent and genetic toolbox. However, adult mice do not robustly transmit SARS-CoV-2. Here we establish a model based on neonatal mice that allows for transmission of clinical SARS-CoV-2 isolates. We characterize tropism, respiratory tract r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In addition to quantifying RNA copy numbers, which can be misleading with RNA viruses, our experiments also quantify infectious viruses. While several useful animal models have been developed to study SARS-CoV-2 ( 14 , 15 ), we find that our patient-derived nasal epithelia model more faithfully reflects replication kinetics in the human nose, the first site of infection.…”
Section: Introductionmentioning
confidence: 84%
“…In addition to quantifying RNA copy numbers, which can be misleading with RNA viruses, our experiments also quantify infectious viruses. While several useful animal models have been developed to study SARS-CoV-2 ( 14 , 15 ), we find that our patient-derived nasal epithelia model more faithfully reflects replication kinetics in the human nose, the first site of infection.…”
Section: Introductionmentioning
confidence: 84%
“…Additionally, 30% of hACE2 KI C57BL/6 mice were seropositive for SARS-CoV-2 antibodies through exposure to respiratory droplets, and successful aerosol inoculation of hACE2 mice required elevated viral concentrations [ 114 ]. Rodriguez et al demonstrated that neonatal K18-hACE2 mice aged 4-7 days could release the virus and transmit it among siblings within the same litter, resulting in a 100% mortality rate among the exposed pups [ 115 ].…”
Section: Animal Models Of Covid-19mentioning
confidence: 99%
“…Analogous to the inactivation of MHV ORF2 in our system, SARS-CoV-2 ORF8 has acquired premature stop codons in numerous globally successful lineages, including B.1.1.7, XBB.1, XBB.1.5, XBB.1.9, and XBB.1.16., as anecdotally described. ORF8 has been of interest since early in the SARS-CoV-2 pandemic due to a small deletion that emerged in its SARS-CoV ortholog in 200325 , an early cluster of infections in Singapore involving an ORF8 deletion variant26,27 , as well as debate over its role during SARS-CoV-2 infection 6,[27][28][29][30][31][32][33][34] . Despite the intense focus on ORF8 function and loss of full-length protein synthesis, very little attention has been devoted to the evolution of the gene itself.…”
mentioning
confidence: 99%